The effect of Collins application on the creative thinking of basic stage students from the teachers' point of view - rasha sami (Journal of Science and Knowledge Horizons, 2023)
This study aimed to recognize the impact of Collins application on the creative thinking skills of stage students from public school teachers' point of view, recognize the pros and cons of applying it.  This study use a questionnaire was prepared that included (25) items, It was distributed randomly . The study sample (348) teachers of basic stage students in public schools in the Jordan. The results of the study are that the degree of the was average. The field of fluency ranked first with a large degree, the field of organization ranked second with a medium degree, and the field of solution Problems ranked third with a medium degree, the field of originality ranked fourth with a moderate degree, and the field of flexibility. Ranked fifth with an average degree. The study showed that there are differences due to the effect of sex in favor of males, and the lack of. There are differences due to the variables of qualification and experience. The study showed the pros and cons of the Collins application .On the creative thinking skills of basic stage students from the point of view of teachers Positives & quot; Developing the ability to research and creativity, discovering and nurturing individual capabilities & quot;  In the first place, either Where the negatives came from the paragraph “Collins’ curricula need further review and development by experts and specialists. ”in the first place. The study recommended that the Ministry of Education in Jordan should pay great attention to Collins. And the need to focus on the creative thinking skills of students, and to include them in the curricula, and to conduct Similar studies at different stages of study.